BIBLIOMETRIC ANALYSIS OF THE INTEGRATION OF RENEWABLE ENERGY IN LEAN MANUFACTURING PRODUCTION SYSTEMS - Putri Bintang Lubis; Putri Najiha; Bintang (Journal Of Renewable Energy Engineering, 2026)
This study presents a bibliometric analysis of the integration of renewable energy into lean manufacturing production systems using Scopus-indexed data from 2022 to 2026. The objective is to map research trends, identify dominant thematic clusters, and examine existing research gaps at the intersection of operational efficiency and energy sustainability. A total of over 1,400 documents were analyzed using VOSviewer to construct keyword co-occurrence networks and thematic maps. The findings reveal four major research clusters: (1) lean manufacturing and sustainable development, (2) Industry 4.0 and digital twins, (3) production control and optimization, and (4) hydrogen production and renewable energy systems. Despite stable publication trends in both lean manufacturing and renewable energy domains, the results indicate weak structural connections between the two fields, suggesting limited integrative research. This study highlights a significant research gap in combining lean operational principles with renewable energy applications, particularly in real-world manufacturing contexts and developing countries. It contributes by providing a comprehensive bibliometric mapping and proposing future research directions that integrate lean efficiency with sustainable energy metrics within interdisciplinary production system frameworks.